A new vocabulary for cultural–economic geography?. Issue 1 (March 2019) - Cook, Ian
Ibert et al.'s (2019) article is a welcome stimulus to, and a refocusing on, what seem to us to be reasonably well-established problematics and debates. Its arguments seem familiar to us because of our work, since 2011, on thefollowthethings.com project. From this perspective, their remit for new cultural–economic geography research doesn't seem cultural enough (what about cultural geography's recent 'turn' towards creative practice?), the publications drawn upon seem unnecessarily traditional (what about geography's ongoing 'turn' towards digital practice and 'natively digital' outputs?), and the research practices needed for the work that is outlined seem undeveloped (what can we learn about capitalism's 'dark' places and strategies of association and dissociation from, among others, creative digital practice?). Digital outputs such asfollowthethings.com risk being bypassed by more traditional practices of academic review, and our insistence that it should 'stand on its own' without accompanying academic papers doesn't, admittedly, help. So, in this response, we have chosen to engage with the anchor article's main themes and arguments by sketching out our parallel world of ongoing research in which strategies and vocabularies of dissociation feature strongly. What we conclude is that both of our projects could be seen to be working towards the same goal: to assemble a new vocabulary that is better suited for the analysis of this area of cultural–economic geography. We'd like to collaborate on this with Ibert et al. ((2019) Geographies of dissociation: value creation, 'dark' places, and 'missing' links. Dialogues in Human Geography. ) and anyone else who's interested.